Evaluating design decisions in real-time using operations modelling - Schumann, B.; Scanlan, J. P.; Takeda, K.; Takeda, Kenji (2nd International Air Transport and Operations Symposium, Delft, NL, 28 - 29 Mar 2011., 2011)
Contemporary design processes of large aerospace products are rigidly focused on customer specifications in order to meet their expectations. Life cycle costs, design space exploration and value engineering are neglected, often leading to substantial cost overruns and delivery delays. Moreover, customer specifications are not scrutinized and design decisions are made ignoring potential operational knowledge. Value-driven design suggests a new approach using flexible customer specifications in order to find optimal designs by exploring the solution space. One aspect of this optimization is the simulation of the anticipated operational life of a product in order to gain operational knowledge and analyse customer specifications. This paper suggests that an operational simulation can be used actively or reactively by designers during the design process to improve a product. It is investigated how an operational simulation can act as a design decision support tool and how it can react to customer specifications. Answers are presented by means of a simulation model recreating the operational life of a Search-and-Rescue Unmanned Air Vehicle developed in parallel at the University of Southampton. The simulation's ability for acting as a decision support tool is explored by conducting a fuel tank size optimization. Reactive capabilities are explored by calculating the surplus value of using UAVs. This exemplifies the derivation of product specifications as the simu-lation reveals the value and hence usefulness of given customer specifications. It is shown that operational simulations benefit designers and overall product value by analysing product specifications and guiding designers to more informed design decisions